Higher-order connections between stereotyped subsets: implications for improved patient classification in CLL - Agathangelidis, Andreas; Chatzidimitriou, Anastasia; Gemenetzi, Katerina; Giudicelli, Veronique; Karypidou, Maria; Plevova, Karla; Davis, Zadie; Yan, Xiao-Jie; Jeromin, Sabine; Schneider, Christof; Pedersen, Lone Bredo; Tschumper, Renee C; et al. (Blood, 2021)
Chronic lymphocytic leukemia (CLL) is characterized by the existence of subsets of patients with (quasi)identical, stereotyped B-cell receptor (BcR) immunoglobulins. Patients in certain major stereotyped subsets often display remarkably consistent clinicobiological profiles, suggesting that the study of BcR immunoglobulin stereotypy in CLL has important implications for understanding disease pathophysiology and refining clinical decision-making. Nevertheless, several issues remain open, especially pertaining to the actual frequency of BcR immunoglobulin stereotypy and major subsets, as well as the existence of higher-order connections between individual subsets. To address these issues, we investigated clonotypic IGHV-IGHD-IGHJ gene rearrangements in a series of 29 856 patients with CLL, by far the largest series worldwide. We report that the stereotyped fraction of CLL peaks at 41% of the entire cohort and that all 19 previously identified major subsets retained their relative size and ranking, while 10 new ones emerged; overall, major stereotyped subsets had a cumulative frequency of 13.5%. Higher-level relationships were evident between subsets, particularly for major stereotyped subsets with unmutated IGHV genes (U-CLL), for which close relations with other subsets, termed "satellites," were identified. Satellite subsets accounted for 3% of the entire cohort. These results confirm our previous notion that major subsets can be robustly identified and are consistent in relative size, hence representing distinct disease variants amenable to compartmentalized research with the potential of overcoming the pronounced heterogeneity of CLL. Furthermore, the existence of satellite subsets reveals a novel aspect of repertoire restriction with implications for refined molecular classification of CLL.
Keywords: frekvence genu; Gene Rearrangement; Humans; Leukemia, Lymphocytic, Chronic, B-Cell; Gene Frequency; lidé; genová přestavba; Immunoglobulin Variable Region; Somatic Hypermutation, Immunoglobulin; somatická hypermutace imunoglobulinových genů; Immunoglobulin Heavy Chains; chronická lymfatická leukemie; těžké řetězce imunoglobulinů; variabilní oblast imunoglobulinu